Magnetic Isinglass a Nano‐Bio Support for Copper Immobilization: Cu–IG@Fe3O4 a Heterogeneous Catalyst for Triazoles Synthesis. Issue 19 (23rd May 2018) - Dolatkhah, Zahra; Javanshir, Shahrzad; Bazgir, Ayoob; Mohammadkhani, Abolfazl
Abstract: A green magnetically heterogeneous catalyst was prepared by the copper immobilization onto magnetic isinglass as a nano bio‐support. The prepared catalyst was used as an effective and reusable catalyst for click synthesis of triazoles by the three‐component reaction of benzyl halide or phenacyl bromides, aryl acetylenes and sodium azide in water as the best green solvent. Abstract : A novel magnetic copper catalyst heterogenized on isinglass has been successfully used in the Huisgen cycloaddition. Reactions took place in the benign aqueous solvent. The catalyst is quite effective and easily magnetically separable.